"Wood Already Touched by Fire is not Hard to Set Alight"; Comment on "Constraints to Applying Systems Thinking Concepts in Health Systems: A Regional Perspective from Surveying Stakeholders in Eastern Mediterranean Countries" - Irene Akua Agyepong (Kerman University of Medical Sciences, 2015)
A major constraint to the application of any form of knowledge and principles is the awareness, understanding and acceptance of the knowledge and principles. Systems Thinking (ST) is a way of understanding and thinking about the nature of health systems and how to make and implement decisions within health systems to maximize desired and minimize undesired effects. A major constraint to applying ST within health systems in Low- and Middle-Income Countries (LMICs) would appear to be an awareness and understanding of ST and how to apply it. This is a fundamental constraint and in the increasing desire to enable the application of ST concepts in health systems in LMIC and understand and evaluate the effects; an essential first step is going to be enabling of a wide spread as well as deeper understanding of ST and how to apply this understanding.